Food safety: a critical part of the food system in Africa: Reader for Brussels Briefing 52 - Boto, Isolina; Mofolo, Lebo (Technical Centre for Agricultural and Rural Cooperation, 2018)
Food safety is linked, directly or indirectly, to the achievement of many of the Sustainable Development Goals (SDGs), especially those pertaining to ending hunger and poverty, and promoting good health and well-being. Food and nutritional security is realized only when essential elements of a healthy diet are safe to eat. The information in this document was compiled as background reading material for the 52nd Brussels Briefing on Food safety: a critical part of the food system in Africa.